Feasibility of cortical bone trajectory screws for bridging fixation in revision surgery for lumbar adjacent segment degeneration. Issue 28 (16th July 2021) - Wang, Long; Zhao, Yong-Hui; Cai, Xing-Bo; Liang, Jin-Long; Luo, Hao-Tian; Ma, Yu-Long; Xu, Yong-Qing; Lu, Sheng
Abstract: Background: To investigate the feasibility of using cortical bone trajectory (CBT) screws for bridging fixation in revision surgery for lumbar adjacent segment degeneration and to provide a reference for clinical practice. Methods: Computed tomography scans of the lumbar spines of 36 patients in our hospital were used. Sixteen males and 20 females with an average age of 65.5 ± 10.5 years (range: 46 to 83 years) were included. Three-dimensional reconstruction was performed using computer software. Screws with appropriate sizes were selected for the L1 to L5 vertebral segments, and traditional pedicle screws were placed using the standard method. After completing screw placement, simulated placement of CBT screws was performed separately. No overlap occurred between the two screws in the process of CBT screw placement, and the placement point and direction were adjusted until screw placement completion. After all screw placement simulations were complete, according to the contact area of the cortical bone of the screw trajectory and the screw puncture position and distance through the trajectory, the screw placement results were categorized as excellent, good, general, and failure. Excellent and good ratings were considered successful, while a general rating was regarded as acceptable. Then, the success rate and acceptable rate of each segment of the lumbar spine were calculated. Results: Three hundred and sixty screw placement simulations were performed in lumbar pedicles, and 72 CBT screws were implanted in each vertebral body of the lumbar spine. The success rates in the L1 to L5 segments were 73.6%, 80.6%, 83.3%, 88.9%, and 77.8%, respectively, and the acceptable rates were 91.7%, 97.2%, 97.2%, 100%, and 91.7%, respectively. The overall success rate and acceptable rate of CBT screw placement in the lumbar spine were 80.8% and 95.6%, respectively. Conclusion: CBT screws are feasible for bridging fixation in lumbar adjacent segment degeneration revision surgery, and the accuracy of screw placement in different lumbar vertebrae varies.